Mapping with(out) borders: an exploratory cartography of cross-border cooperation in the Spanish-Portuguese raya/raia - Heriberto Cairo; María Lois; Pedro Limón; Sergio Claudio González; Joan Bauzà (Journal of Maps)
Cross-border cooperation has developed fundamentally at the internal borders of the European Union. The border between Spain and Portugal, known as the line (raya in Spanish and raia in Portuguese), is one of them. Numerous cooperation projects have been developed there in recent years, although with a heterogeneous geographical distribution. The border seems to disappear, but far from doing so, it is just transformed, as the study of the dimension of national security shows, which is now largely binational. One of the highest levels of cross-border cooperation that has been achieved is that of integrated local units, called eurocities, with diverse objectives. We address the study of various dimensions of this eurocities with the aim of better understanding where they are created, in what political context and what is their demographic, economic and cultural impact.